The gradual reduction of viroid levels in hop mericlones following heat therapy: a possible role for a nuclease degrading dsRNA - Matousek, J; Trnĕná, L; Svoboda, P; Oriniaková, P; Lichtenstein, C P (Biological chemistry Hoppe-Seyler, 1995)
A high concentration of hop latent viroid (HLVd) was detected in infected mericlones of Osvald's hops grown in vitro. This concentration was about 8-fold higher than in leaves of young, field-grown plants, reaching about 30 pg/mg of fresh mass. Treatment of these in vitro-grown plants at high temperature (35 degrees C) for two weeks lead to a dramatic (about 70-90%) decrease of HLVd content. More detailed investigations performed with mericlone 6147 of Osvald 31 showed that HLVd levels decrease gradually during subsequent cycles of heat treatment. A nuclease activity capable of cleaving HLVd and fully double-stranded RNA was shown to increase significantly in hop tissues during thermotherapy cycles, or after the heat shock. The nuclease activity was found to have similar properties to those extracted earlier from tobacco anthers. This enzyme resembles a sugar-unspecific nuclease which has a maximum activity at pH 5.5. Analysis of the activity with viroid and dsRNA showed that both, endo- and exonucleolytic activities were attributable to the enzyme. A strong tissue-specific gradient of viroid (the lowest level in stem apex and the highest level in roots) was observed in young plants, showing a negative correlation with the dsRNAse activity. In senescent plants, the highest viroid concentration was observed in maturated cones and in upper stems. High nuclease activity in the upper stem tissue suggests that viroid RNA must be protected in this tissue against degradation.
Keywords: viroidy; hybridizace in situ; gelová chromatografie; Hot Temperature; Plant Diseases; Chromatography, Gel; Culture Techniques; kultivační techniky; RNA, Double-Stranded; koncentrace vodíkových iontů; Meristem; In Situ Hybridization; Plant Physiological Phenomena; Viroids; Plants; vysoká teplota; fyziologie rostlin; Ribonucleases; dvouvláknová RNA; nemoci rostlin; meristém; rostliny; ribonukleasy; Hydrogen-Ion Concentration